2020
DOI: 10.18280/ijht.380121
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hydrodynamic Performance of Fluid Flow in a Rectangular Channel Using Baffles with Gaps

Abstract: In the present analysis, a new geometry of obstacles is considered in order to demonstrate its importance in improving the thermal-hydrodynamic performance of hydrogen fluid within a 2D, rectangular section channel subject to a constant surface temperature condition along its hot top wall. The new obstacle has a variable-position square-shaped gap (called: perforated obstacle), to reduce its resistance to the fluid flow, to decrease the skin friction, in order to determine the optimum configuration for a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The results showed that the use of SiO2-EG at a volume fraction of 6% and of 800 results in a higher average Nusselt number of about 50% compared to the case of using =100. Other interesting analysis of the effect of different techniques with and without nanofluids on enhancing heat transfer can be found in references [24][25][26]. Many studies investigated the effect of hydrodynamics on fish locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the use of SiO2-EG at a volume fraction of 6% and of 800 results in a higher average Nusselt number of about 50% compared to the case of using =100. Other interesting analysis of the effect of different techniques with and without nanofluids on enhancing heat transfer can be found in references [24][25][26]. Many studies investigated the effect of hydrodynamics on fish locomotion.…”
Section: Introductionmentioning
confidence: 99%